Single Artery Upper Extremity Salvage with Two Free Flap End-to-Side Brachial Artery Anastomoses - Stein, Michael J.; Zhang, Jing (Journal of Reconstructive Microsurgery Open, 2020)
Background A 36-year-old male was involved in a motor vehicle accident, presenting with a Guistillo's IIIB crush injury to the upper extremity. A severely comminuted ulnar fracture resulted in a 10-cm bone defect with significant overlying soft tissue injury.Methods The injury resulted in a wide zone of injury with inadequate collateral vascularity at the level of the elbow and distal viability dependent on the brachial artery. An osteocutaneous free fibular flap and fasciocutaneous anterolateral thigh flap were used to reconstruct the defect with both flaps anastomosed in an end-to-side fashion to the brachial artery.Results The upper extremity was successfully salvaged, and the patient discharged from hospital at postoperative day 10. Both free flaps survived with no donor or recipient site complications at a follow-up period of 2 years.Conclusion The case illustrates the challenges inherent to significant Guistillo's IIIB injuries with insufficient recipient vessels over a large zone of injury. While performing anastomoses outside the zone of injury is preferred, this case demonstrates the success of performing multiple anastomoses to the brachial artery in an end-to-side fashion within the zone of injury.
Keywords: trauma; upper extremity reconstruction; end to side anastomosis